Enhancing Light–Matter Interactions in MoS2 by Copper Intercalation. Issue 23 (6th May 2021) - Stern, Chen; Twitto, Avraham; Snitkoff, Rifael Z.; Fleger, Yafit; Saha, Sabyasachi; Boddapati, Loukya; Jain, Akash; Wang, Mengjing; Koski, Kristie J.; Deepak, Francis Leonard; Ramasubramaniam, Ashwin; Naveh, Doron
Abstract: The intercalation of layered compounds opens up a vast space of new host–guest hybrids, providing new routes for tuning the properties of materials. Here, it is shown that uniform and continuous layers of copper can be intercalated within the van der Waals gap of bulk MoS2 resulting in a unique Cu–MoS2 hybrid. The new Cu–MoS2 hybrid, which remains semiconducting, possesses a unique plasmon resonance at an energy of ≈1eV, giving rise to enhanced optoelectronic activity. Compared with high‐performance MoS2 photodetectors, copper‐enhanced devices are superior in their spectral response, which extends into the infrared, and also in their total responsivity, which exceeds 10 4 A W −1 . The Cu–MoS2 hybrids hold promise for supplanting current night‐vision technology with compact, advanced multicolor night vision. Abstract : Intercalation of uniformly distributed copper into the van der Waals gap of vertically aligned MoS2 grown by chemical vapor deposition improves photodiode device performance. The intercalated MoS2 remains semiconducting and possesses a unique plasmon resonance at an energy of ≈1 eV. Remarkably enhanced photoresponse from the ultraviolet to near‐infrared regime is presented.